Sex, gender, and episcopal authority in an age of reform, 1000-1122 - MacLaughlin, Megan (Cambridge University Press, 2010)
The reform of marriage -- The bride of Christ -- The ambiguities of motherhood -- The mother of the faithful -- Fathers and sons -- Fathers in the Spirit -- Conclusion : the stumbling block